2023
DOI: 10.3389/fbioe.2023.1081446
|View full text |Cite
|
Sign up to set email alerts
|

Implantable biomedical materials for treatment of bone infection

Abstract: The treatment of bone infections has always been difficult. The emergence of drug-resistant bacteria has led to a steady decline in the effectiveness of antibiotics. It is also especially important to fight bacterial infections while repairing bone defects and cleaning up dead bacteria to prevent biofilm formation. The development of biomedical materials has provided us with a research direction to address this issue. We aimed to review the current literature, and have summarized multifunctional antimicrobial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 177 publications
0
4
0
Order By: Relevance
“…The hydroxyapatite nanoparticles used in this study, with a diameter of 25 nm, can cross the blood barrier of the spinal cord and can be maintained for a long time, after injection, with a stable drug release. The loading of chABCI on hydroxyapatite nanoparticles does not require hard processing, and hydroxyapatite is a biocompatible material with the ability to guide bone growth, minimally stimulating the immune system, and minimally swelling, and it has been used in the treatment of bone infections before (Shuaishuai et al 2023 ). Previous studies showed that the extraction and purification of the enzyme from Proteus vulgaris bacteria are done as an important source of the chABCI.…”
Section: Discussionmentioning
confidence: 99%
“…The hydroxyapatite nanoparticles used in this study, with a diameter of 25 nm, can cross the blood barrier of the spinal cord and can be maintained for a long time, after injection, with a stable drug release. The loading of chABCI on hydroxyapatite nanoparticles does not require hard processing, and hydroxyapatite is a biocompatible material with the ability to guide bone growth, minimally stimulating the immune system, and minimally swelling, and it has been used in the treatment of bone infections before (Shuaishuai et al 2023 ). Previous studies showed that the extraction and purification of the enzyme from Proteus vulgaris bacteria are done as an important source of the chABCI.…”
Section: Discussionmentioning
confidence: 99%
“…4 Traditional treatment strategies for infected bone defects include thoroughly clearing the wound, implanting antibioticimpregnated cement spacers, and administering antibiotics. 5 However, the efficacy of systemic antibiotic administration is significantly undermined by the infection-induced disruption of the local blood supply and the resulting onset of osteonecrosis. This severely limits the effective concentration of antibiotics at the site of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the prolonged and widespread use of antibiotics has led to the gradual evolution of bacterial resistance and the emergence of highly resistant strains of bacteria. 5 Therefore, alternative materials with antibacterial properties are being investigated. Among them, metal–organic frameworks (MOFs) are becoming increasingly prominent in this aspect.…”
Section: Introductionmentioning
confidence: 99%
“…Among these, bone grafting is the most important clinical treatment of infectious bone defects. Because the operation is simple, there are few postoperative complications and good fracture healing, and bone grafting can be used to treat infectious bone defects with segmental and large bone defects [ 16 ]. In addition, when the transplant material fills the bone defect, it can control the infection through an efficient bacteriostatic strategy, induce the formation of fibrous membranes, provide good blood transport, and form a relatively independent and stable space at the bone defect, which is conducive to secondary bone reconstruction and bone healing, and effectively improves the osteogenesis of cancellous bone [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%